Carolina Abecedarian Project and the Carolina Approach to Responsive Education (CARE), 1972-1992 - Ramey, Craig T. ([Verlag nicht ermittelbar], 2004)
The data come from two consecutive longitudinal studies on the effectiveness of early childhood educational intervention for children at high risk for developmental delays and school failure. The projects are the Abecedarian Project and a related study, the Carolina Approach to Responsive Education (CARE). Combined, the two studies test the hypothesis that child care, home visit, and home school resource interventions can enhance cognitive and academic outcomes for children at risk for school failure due to factors such as poverty, low maternal IQ, or low parental education. The study is a prospective randomized trial with participants from low-income families either participating in the planned "treatment" groups or serving as untreated controls. All have been followed from birth to adolescence. These studies provide the only experimental data regarding the efficacy of child care interventions that began during early infancy and lasted until the child entered kindergarten. In addition, the data allow for tests of the efficacy of intervention during the primary grades. The Abecedarian Project recruited children born between 1972 and 1977. At entry to school, half of the children within each of the two randomized preschool groups were randomly assigned to receive a home school resource teacher program during the first three years of elementary school. Children recruited for Project CARE (Carolina Approach to Responsive Education), however, were born between 1978 and 1980 and randomly assigned to one of three treatment groups: child care plus home visits, home visits only, or control. All Project CARE children assigned to either the child care plus home visit or home visit only groups also received the home school resource teacher treatment during the first three years of elementary school. Essentially, three educational treatments were provided: educational child care from six weeks to school entry, home visit from six weeks to school entry, and home school resource services during the child's first three years of school. They varied in terms of intensity and orientation. The child care treatment was essentially child-centered and offered the most intensive exposure to education. It involved the child receiving child care at the child development center from infancy until entry to kindergarten. The home visit and home school treatments were less intensive and were family-oriented, emphasizing the role of the parent as a change agent in the child's development. Participants were tested based on four different measurement scales: maternal measures, quality of the family environment, cognitive assessment, and academic achievement. The maternal measures include variables such as marital status, maternal and paternal age, education, and family socioeconomic status. The cognitive assessments include the Bayley Scales of Infant Development at 3, 6, 9, 12, and 18 months, the Stanford-Binet Intelligence Scale at 24, 36, and 48 months, the McCarthy Scales of Children's Abilities at 30, 42, and 54 months, the Wechsler Preschool and Primary Scale of Intelligence at 60 months, and the Wechsler Intelligence Scale for Children-Revised (WISC-R) at 6.5, 8, 12, and 15 years. Some of the tests were administered in only one study for a particular age. These include the Mental Development Index (MDI) at 3 and 9 months and WISC-R at 15 years (Abecedarian only). Some achievement tests such as Peabody Individual Achievement Test (PIAT) were administered in the fall and spring of the first two years of public school (kindergarten and first grade if the child was at grade level both years) for the Abecedarian Project. The Woodcock-Johnson was administered in the fall and spring of the Abecedarian child's third year of school, in the summer following their seventh and tenth years of school, in the fall and spring of the Project Care child's first three years of school, and in the summer following their seventh year of school.